Structural Remodeling of the Extracellular Matrix in Arteriogenesis: A Review - Kulkarni, Rohan; Andraska, Elizabeth; McEnaney, Ryan (Frontiers in Cardiovascular Medicine, 2021)
Lower extremity arterial occlusive disease (AOD) results in significant morbidity and mortality for the population, with up to 10% of patients ultimately requiring amputation. An alternative method for non-surgical revascularization which is yet to be fully understood is the optimization of the body’s own natural collateral arterial network in a process known as arteriogenesis. Under conditions of conductance vessel stenosis or occlusion resulting in increased flow, shear forces, and pressure gradients within collaterals, positive remodeling occurs to increase the diameter and capacity of these vessels. The creation of a distal AVF can drive increased arteriogenesis as compared to collateral formation with the occlusion of a conductance vessel alone by further increasing flow through these arterioles, demonstrating the capacity for arteriogenesis to form larger, more efficient collaterals beyond what is spontaneously achieved after arterial occlusion. Arteries rely on an extracellular matrix (ECM) composed of elastic fibers and collagens that provide stability under hemodynamic stress, and ECM remodeling is necessary to allow for increased diameter and flow conductance in mature arterial structures. When positive remodeling occurs, digestion of lamella and the internal elastic lamina (IEL) by matrix metalloproteinases (MMPs) and elastases results in the rearrangement and thinning of elastic structures, and may be replaced with disordered elastin synthesis without recovery of elastic function. This results in transmission of wall strain to collagen and potential for aneurysmal degeneration along collateral networks, as is seen in the PDA after celiac occlusion and IMA with concurrent celiac and SMA occlusions. Further understanding into the development of collaterals is required to both better understand aneurysmal degeneration and optimize collateral formation in AOD.